Auditors switching in the relationship between corporate governance and financial performances - evidence from Malaysian Public Listed Companies (PLCs) - Ik, Yee Tan; Tze, San Ong; Lee , Lee Chon; Samuel, Adedeji Babatunji (Faculty of Economics and Management, Universiti Putra Malaysia, 2016)
Due to the corporate scandals in the business world, corporate governance is big concern and becomes an alarming issue. Bursa Malaysia required all PLCs to have corporate disclosures in order to cultivate sound corporate governance, meanwhile auditors act as watchdogs in ensuring the disclosures. However, auditor switching is evident and disorder of auditor switching often takes place in Malaysia. Thus, this paper seeks to empirically investigate the association between corporate governance, auditor switching, and financial performance of Malaysian PLCs. Secondary data on a total number of 100 PLCs from years 2009 to 2013 are used. The results reveal that separation of position for BOD chairman and CEO as well as large board size lead to better overseeing of the management on behalf of shareholders, which drives the firm performance. Surprisingly, independent directors do not definitely lead to good firm performance, especially when they do not play their role properly. When there is CEO/chairman duality, tendency of auditor switching is low due to a long-tenure relationship with auditor. A high powered structure in Malaysia that concentrates on top-down relationship prompts no objection from board members and independent directors when a less crucial decision such as auditor switching decision is made. Auditors as the mediator play significant roles between corporate governance and financial performance since they provide creditability and greater assurance to investors. Therefore, this paper has vital implications and gives insight for government to emphasize the auditors’ roles as agents for ensuring impacts on the association between corporate governance and financial performance.